ANALYSIS OF THE POTENTIAL DEVELOPMENT OF MANGROVE FOREST ECOTOURISM IN KAMPUNG SUNGAI KAYU ARA, SIAK DISTRICT, RIAU PROVINCE - Dessy Yoswaty; Irwan Effendi; Nursyirwani Nursyirwani; Joko Samiaji; Muhammad Razali (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The mangrove forest ecosystem in Sungai Kayu Ara Village, Sungai Apit Subdistrict, Siak Regency, Riau Province has a unique or distinctive appeal, which has the potential to be developed as a mangrove forest ecotourism destination. The research objective was to analyze the potential for developing mangrove forest ecotourism in Sungai Kayu Ara Village in realizing sustainable mangrove forest conservation. The method used in this research is the survey method, which was carried out in May-July 2020. Mangrove density data was taken using the line transect plot technique, which consists of 3 observation transects. Each transect has 3 plots, each plot measuring 10 x 10 m2. The identification results found 6 types of mangroves that grow in the mangrove forest area of Sungai Kayu Ara Village, namely Rhizophora apiculata, Avicennia alba, Bruguiera gymnorrihiza, Sonneratia alba, Nypa fruticans, and Xylocarpus granatum. The mangrove density value is 1234 ind / ha. The average value of the Tourism Suitability Index (IKW) is 76.75%. (S2 category), which is suitable for development as a mangrove forest ecotourism area. Mangrove forest ecotourism development strategies based on SWOT analysis include 1) Increasing stakeholder cooperation for mangrove forest conservation; 2) Developing facilities and infrastructure for the development of mangrove forest ecotourism; 3) Provision of information and promotion of manrove ecotourism through print and electronic media; and 4) Increased quality of skilled and skilled human resources for the development of mangrove forest ecotourism.